Olive Oil Processing, Characterization, and Health Benefits - Boskou, Dimitrios; Clodoveo, Maria Lisa (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Mediterranean diet is well-known worldwide and recognized as a nutrition reference model by the World Health Organization. Virgin olive oil, prepared from healthy and intact fruits of the olive tree only by mechanical means, is a basic ingredient and a real pillar of this diet. Its positive role in health has now been a topic of universal concern. The virtues of natural olive oil, and especially of extra virgin olive oil, are related to the quality of the fruits, the employment of advanced technologies, and the availability of sophisticated analytical techniques that are used to control the origin of the fruits and guarantee the grade of the final product. To enrich recent multidisciplinary scientific information concerning this healthy lipid source, a new special issue of Foods has been published.